Surface AFM microscopy of unworn and worn samples of silicone hydrogel contact lenses - González-Méijome, José Manuel (2009)
Abstract: Purpose. To evaluate the qualitative and quantitative topographic changes in the surface of worn contact lenses (CLs) of different materials using atomic force microscopy (AFM). Methods. The topography of five different CL materials was evaluated withAFM over a surface of 25 lm2 according to previously published experimental setup. Average roughness (Ra) and root mean square (Rms) values were obtained for unworn and worn samples. Results. The Ra value increased for balafilcon A (11.62–13.68 nm for unworn and worn samples, respectively), lotrafilcon A (3.67–15.01 nm for unworn and worn samples, respectively), lotrafilcon B (4.08–8.42 nm for unworn and worn samples, respectively), galyfilcon A (2.81–14.6 nm for unworn and worn samples, respectively), and comfilcon A (2.87–4.63 nm for unworn and worn samples, respectively). Differences were statistically significant for all lenses except Rms and Ra for comfilcon A, and Ra parameter for balafilcon A (p > 0.05). The least relative increase was observed for some balafilcon A samples and for some of these samples the roughness decreased after the lenses had been worn. Conclusion. The changes in surface roughness between unworn and worn lenses are different for different silicone-hydrogel materials. Overall all CLs increased the degree of surface roughness after being worn, even for very short periods of time. However, for samples of balafilcon A, roughness increases at a lower extent or even can decrease as compared to unworn samples of the same material due to filling of the macropores.